Waclaw Radecki: Proposing a new narrative for an old character - Fonseca, Luiz E. P. (Revista de Psicología, 2019)
Waclaw Radecki is an important character in South American history of psychology, being the founder and manager of laboratories of psychology in both Brazil and Uruguay, having also founded institutes of psychology in said countries and Argentina. Author of many books regarding psychology, and specifically about his psychological system, affective discriminationism (to this day remaining only partially comprehensible), Radecki remains a char-acter whose history is confunsing in some aspects. Having his life narrated by a biography in Poland, a famous paper in Brazil about his passage there and few texts regarding his last days in Uruguay and Argentina, this paper proposes a new narrative about this character, tracing his life since birth in Poland, in 1887, until death in Uruguay in 1953, trying to clarify obscure aspects in current texts, verifying dates and answering questions that remain a mistery, such as the reason for his moving from Poland to Brazil, his troubled moving to Uruguay and Argentina, and his last days as the leader of the school of affective discrimination. The paper proposes a historical narrative about Radecki utilizing new sources, such as documents, books and newspapers largely unexplored by South American historians of psychology.